Norwegian Frozen Tours: Analytical Translation of Tourism Text and Landscape - Hanifah, Aulia; Afriliani, Afriliani (Transpublika Publisher, 2024)
Along with the popularity of Frozen 2 which later became the branding of Norwegian tourism, interest in tourism texts also increased. Therefore, researcher seek to what extent translated texts and visual analysis convey meaning. This research analyzed textual and visual tourism text titled “The Places in Norway that Inspired Frozen 2” from the visitnorway.com site. The purpose of this research are: (1) to understand the application of translation method in the tourism text analyzed, and (2) to understand the process of visual analysis of the illustrations in the tourism text analyzed. In this research, communicative translation that emphasize the transfer of contextual meaning from the source text into the target text is the most appropriate method to apply on the translation of the informative language tourism text. As for visual analysis in exploring general information related to the illustrations in the tourism text that could produce picture descriptions that support the need of information the source text author was to convey. Based on the application of these communicative translation method and visual analysis, results have shown that both are able to convey the meaning and purpose of the tourism text, which is to attract tourists to visit Norway by introducing nature and culture through its relevance to the Frozen film.